PARTISIPASI POLITIK ANGGOTA DPRD DALAM PEMBUATAN PERATURAN DAERAH PADA DPRD KOTA SORONG - Salmawati Salmawati; Arie Purnomo; Herman Dema (PRAJA: Jurnal Ilmiah Pemerintahan, 2023)
This research aims to examine the political participation of members of the Sorong City DPRD in the making of local regulations. The research adopts a qualitative approach with data collection techniques through in-depth interviews and participatory observation. Respondents in this study are members of the Sorong City DPRD and relevant parties in the process of making local regulations. The results indicate that the political participation of members of the Sorong City DPRD in the making of local regulations is still low. This is due to various factors such as the limited access to information and the time constraints that DPRD members have to study draft local regulations. In addition, internal DPRD policies that restrict the participation of DPRD members in the process of making local regulations also pose obstacles. Therefore, efforts are needed to increase the political participation of DPRD members in the making of local regulations in Sorong City. Efforts that can be made include expanding access to information and providing training related to the making of local regulations to DPRD members. Additionally, there is a need to change internal DPRD policies that accommodate the participation of DPRD members in the process of making local regulations. It is expected that with increased political participation of DPRD members, the resulting local regulations can be more responsive to the interests of the community